Pengaruh Temperatur Pengeringan Pada Alat Pengering Sistem Rotary Terhadap Kualitas Cabai Merah - Dikki Pratama; Vivi Apriyanti; Generousdi (Jurnal INOVATOR, 2021)
Red chili is a food ingredient that is widely consumed and grown in Indonesia. Prices fluctuate greatly due to many factors. Post-harvest handling of chili can help farmers from losses and can maintain price stability in the market. The easiest post-harvest handling is drying. In this study, chili drying was carried out using a dryer with a rotary system. The dryer is designed in the form of a mechanical rotating drum driven by an electric motor. Hot air from LPG combustion is passed forcibly across the drum using a blower. Drying was carried out for 6 hours with a capacity of 3 kg of fresh red chilies at 60 oC, 70 oC and 80 oC. Drying at a temperature of 60 oC produces a high water content of 18.2 % with a weight loss of 80 %, the texture of the chili is still wet and soft with a bright red color. At a drying temperature of 70˚C the moisture content is quite low, namely 11.22 %, weight loss is about 87.2 %, the texture of dry chili is brightly red colored, while at a temperature of 80 ˚C the water content is low 9.1 %, the weight loss is high 90 %, dry chili texture with brown color.